The Role of Chinese Communities to the Spread of Islam in Indonesia - M. Ikhsan Tanggok (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
The role of Chinese people in the development of Islam in Indonesia in the past was significant, as evidenced by historical evidence such as mosques and Muslim Chinese graves. The spread of Islam in Indonesia was not only carried out by Arabs and Persians, but also by Chinese people, both those who came with traders from the Middle East and separately. Since Islam entered the Malay Archipelago, especially Indonesia, through traders, it is understandable that Islamic kingdoms first emerged in coastal areas rather than inland or mountainous areas, which generally adhered to Hinduism, Buddhism, or local religions and beliefs. Their main purpose for coming to Indonesia was not to spread Islam but to establish relationships and trade. However, because they were Muslims, their attitudes and actions could influence the local population wherever they were, and intermarriages between them and the local population could lead the locals to convert to Islam.